2014
DOI: 10.1016/j.psychres.2014.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Daily life evidence of environment-incongruent emotion in schizophrenia

Abstract: Researchers have recently hypothesized that negative emotion in positive situations may be one mechanism for understanding emotion dysfunction in schizophrenia. Using ecological momentary assessment, we examined the relationship between emotion experience and environmental context in the daily lives of participants with and without schizophrenia. Participants with (n = 47) and without schizophrenia (n = 41) were provided a cellular telephone and called four times a day for one week. During each call participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
6
24
0
Order By: Relevance
“…Previous studies indicated that patients with schizophrenia showed abnormal emotional experience and facial expression recognition (Sanchez et al, 2014 ; Zhu et al, 2016 ); they experienced more negative and less positive emotion than did healthy individuals. Meanwhile, the ability of recognizing positive expressions was weaker in male patients with schizophrenia than in healthy individuals, while the ability of recognizing both positive and negative emotions was similar in female patients with schizophrenia and in healthy individuals.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies indicated that patients with schizophrenia showed abnormal emotional experience and facial expression recognition (Sanchez et al, 2014 ; Zhu et al, 2016 ); they experienced more negative and less positive emotion than did healthy individuals. Meanwhile, the ability of recognizing positive expressions was weaker in male patients with schizophrenia than in healthy individuals, while the ability of recognizing both positive and negative emotions was similar in female patients with schizophrenia and in healthy individuals.…”
Section: Discussionmentioning
confidence: 93%
“…Hartley et al [ 41 ] and So et al [ 42 ] did not find a relationship between symptom severity and dropout; however, Palmier-Claus et al [ 29 ] (also reported in the original study [ 30 ]) found that higher severity on the positive and negative syndrome scale’ (PANSS) positive symptom subscale predicted dropout. Finally, Sanchez et al, [ 43 ] found that the level of cognitive functioning did not predict completion of the study. See Table 10 for a summary.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] Findings from these studies suggest that, surprisingly, deficits in expression and blunted affect in individuals with psychotic disorder are not associated with a reduced intensity of emotional experience in daily life. 30,31,33 However, individuals with schizophrenia and high negative symptoms have been found to show a stronger preference for being alone when in company and more social withdrawal in daily life. 27 Similarly, there is evidence of a greater preference for solitude, increased time alone, and lower positive affect in the daily life of individuals with subclinical social anhedonia.…”
Section: Ecological Interventionist Causal Models In Psychosis Putatimentioning
confidence: 99%